Atrioventricular septal defect: From embryonic development to long-term follow-up. (1st January 2016) - Calkoen, Emmeline E.; Hazekamp, Mark G.; Blom, Nico A.; Elders, Bernadette B.L.J.; Gittenberger-de Groot, Adriana C.; Haak, Monique C.; Bartelings, Margot M.; Roest, Arno A.W.; Jongbloed, Monique R.M.
Abstract: Atrioventricular septal defect (AVSD) covers a spectrum of heart anomalies with a common atrioventricular connection and has an incidence of 4–5.3 per 10.000 live births. About half of the AVSDs occur in patient with Down syndrome. This review provides a bench to bedside overview of AVSD. Developmental aspects, nomenclature, anatomy, and classification of AVSD are discussed. Furthermore an overview of genetic and maternal risk factors for AVSD is provided, and available literature on (fetal) diagnosis, surgical techniques and follow-up is presented. Special attention is given to differences in developmental, anatomical and prognostic factors of AVSD between non-syndromic and Down syndrome patients. Highlights: AVSD comprises a heterogeneous group of congenital defects. Abnormal endocardial cushion, mesenchymal cap and DMP development may result in AVSD. Genetic and maternal risk factors for AVSD and developmental aspects are discussed. AV-valve regurgitation after correction is common and can be assessed with 4DFlow MRI. Non-syndromic and Down syndrome patients have different anatomy and outcome.